2001
DOI: 10.1034/j.1399-3038.2001.012002073.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage in asthmatic children: Evidence of neutrophil activation in mild‐to‐moderate persistent asthma

Abstract: Little information is available on cell profiles and mediator production in the lower airways of children with asthma by comparison with the adult population. To study the bronchoalveolar lavage (BAL) cell profiles and production of eosinophil cationic protein (ECP) and myeloperoxidase (MPO) in childhood bronchial asthma, a retrospective study was performed in 29 children (13 allergic asthmatic children and 16 controls). Six of the asthmatics had mild-to-moderate persistent disease and seven had intermittent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 16 publications
(20 reference statements)
1
29
0
3
Order By: Relevance
“…(13,17) However, various authors have also confirmed the participation of neutrophils in the bronchial inflammation found in asthma patients and, especially, in wheezing infants, (15)(16)(17)(18)(19) regardless of the presence of bacterial infection. Various studies (14,15,18,20) have associated the increase in the number of neutrophils with greater severity of symptoms.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…(13,17) However, various authors have also confirmed the participation of neutrophils in the bronchial inflammation found in asthma patients and, especially, in wheezing infants, (15)(16)(17)(18)(19) regardless of the presence of bacterial infection. Various studies (14,15,18,20) have associated the increase in the number of neutrophils with greater severity of symptoms.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…The role of airway neutrophils in the pathogenesis of persistent asthma despite mild/moderate inhaled corticosteroid (ICS) doses has not been established. However, more recent data confirm considerable heterogeneity of the asthma phenotype and many subjects may exhibit an airway disease characterised by sputum neutrophilia rather than an eosinophilic inflammatory pattern [7][8][9].In-vitro data suggest that long-acting b 2 -agonists (LABAs) may have a neutrophil modulatory effect and such an effect could explain the reductions in asthma exacerbations seen with LABAs [10]. A significant decrease in activated eosinophil numbers in ICS-treated, but still symptomatic, asthmatic subjects following introduction of salmeterol xinafoate has previously been described [11].…”
mentioning
confidence: 99%
“…The role of airway neutrophils in the pathogenesis of persistent asthma despite mild/moderate inhaled corticosteroid (ICS) doses has not been established. However, more recent data confirm considerable heterogeneity of the asthma phenotype and many subjects may exhibit an airway disease characterised by sputum neutrophilia rather than an eosinophilic inflammatory pattern [7][8][9].…”
mentioning
confidence: 99%
“…In the retrospective study, MPO concentrations were significantly raised in children with asthma compared with "controls," with significantly higher levels being found in children with persistent compared with episodic asthma [55]. Although IL-8 levels are reported to be similar in children with asthma, infantile wheeze, and "controls," IL-8 levels increased with the symptom score [57].…”
Section: Neutrophil Numbers and Neutrophil-derived Mediators In The Amentioning
confidence: 96%
“…with episodic asthma [55]. In a prospective study, neutrophils were increased in approximately 33% of children with asthma and 50% of those with infantile wheeze compared with control values, although statistical significance was only found in the latter group [56].…”
Section: Neutrophil Numbers and Neutrophil-derived Mediators In The Amentioning
confidence: 97%